2000
DOI: 10.1074/jbc.m906383199
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 Inhibits Apoptosis Downstream of Cytochrome c Release and Upstream of Caspase-3 Activation

Abstract: Heat shock protein 70 (HSP70) has been shown to act as an inhibitor of apoptosis. We have also observed an inhibitory effect of HSP70 on apoptotic cell death both in preheated U937 and stably transfected HSP70-overexpressing U937 (U937/HSP70) cells. However, the molecular mechanism whereby HSP70 prevents apoptosis still remains to be solved. To address this issue, we investigated the effect of HSP70 on apoptotic processes in an in vitro system. Caspase-3 cleavage and DNA fragmentation were detected in cytosoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
259
1
14

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(287 citation statements)
references
References 57 publications
(43 reference statements)
13
259
1
14
Order By: Relevance
“…Increased Hsp70 expression in tumours also correlates with evasion from apoptosis (Ciocca et al, 1993;Wei et al, 1995;Jaattela, 1999;Kaur et al, 2000). Hsp70 was further shown to inhibit the activation of procaspase-3, but not the activity of processed caspase-3 (Mosser et al, 1997;Li et al, 2000;Mosser et al, 2000;Saleh et al, 2000). Hsp70 was found to associate with Apaf-1 and block the apoptosome-mediated activation of caspase-9, which is an upstream event for caspase-3 activation (Beere et al, 2000;Saleh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Increased Hsp70 expression in tumours also correlates with evasion from apoptosis (Ciocca et al, 1993;Wei et al, 1995;Jaattela, 1999;Kaur et al, 2000). Hsp70 was further shown to inhibit the activation of procaspase-3, but not the activity of processed caspase-3 (Mosser et al, 1997;Li et al, 2000;Mosser et al, 2000;Saleh et al, 2000). Hsp70 was found to associate with Apaf-1 and block the apoptosome-mediated activation of caspase-9, which is an upstream event for caspase-3 activation (Beere et al, 2000;Saleh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have documented that HSP levels increase in the ischemic penumbra of the brain in animal models of focal ischemia, which is an area where many injured neurons survive [19] . It has been reported that gene transfer induced HSP70 overexpression protects neurons from ischemic brain damage in experimental rat stroke models [20] . Additionally, the overexpression of HSP70 inhibits the activation of NF-κB, which is persistently activated during ischemia and appears to promote apoptotic cell death [21] .…”
Section: Discussionmentioning
confidence: 99%
“…54 Using in vitro systems, hsp70 was found to prevent apoptosome formation 55 and caspase 3 activation. 56 In these studies, however, participation of a DnaJ family member(s) was not given attention. Using in vitro systems, King et al 57 showed that the hsc70/dj1 chaperone pair bind to p53 and may regulate the stabilization and localization of p53.…”
Section: Hsp70/dnaj Chaperone Pair Prevents Chop-induced Apoptosis Thmentioning
confidence: 99%